Recognizing Sexually Transmitted Infections And Their Treatment - Nabilla Septiana; Dinie Ramdhani Kusuma; Yunita Hapsari (Rifa'Institute, 2021)
Sexually Transmitted Infections (STIs) are diseases that can be transmitted from one person to another, can be caused by bacteria, viruses, parasites, and fungi. STIs can be transmitted through vaginal, anal, and oral sex. This article aims to identify STIs and their management. The sources used are scientific journals and textbooks. Source searches were conducted on the online portals of journal publications such as the National Center for Biotechnology Information / NCBI (ncbi.nlm.nih.gov) and Google Scholar (scholar.google.com). Transmission of STIs can occur due to interactions between agents (disease-causing factors), hosts (humans as hosts), and the environment (environmental factors). The increase in the incidence of STIs is influenced by several factors, including demographic changes such as very high population growth, increased community movements due to work or tourism, advances in IT-based technology (Technology Information) and socio-economic improvements.